Adoption of E-Tendering System among Small and Medium Enterprises (SME) Contractors in Malaysian Construction Industry - RAFIAN, SITI HAJAR HANISAH; Che Haron , Roziha; MASROM, MD ASRUL NASID (Research in Management of Technology and Business, 2025)
The National Construction Policy 2030 (NCP 2030) was established to improve Malaysia’s public procurement system by introducing a centralized e-procurement platform aimed at enhancing efficiency, productivity, innovation, and transparency. A key aspect of this policy is the shift to e-tendering, which streamlines tender submission, contracting, and trading through online platforms. Despite the potential benefits, the adoption of e-tendering remains a challenge, particularly for Small and Medium Enterprises (SMEs), which face barriers such as resistance to technological change, and limited understanding of the system. Small and Medium-sized Enterprises (SMEs) play a vital role in the construction sector, especially in Malaysia, where they accounted for more than 90% of the sector’s composition and thus provide a greater contribution as a force for economic expansion. This strong implication of overwhelming presence among small and medium enterprises indicates their preeminent role in the construction industry. However, SMEs from the construction industry still lag in terms of adopting web marketing methods which are e-tendering systems. This study aims to explore the adoption of e-tendering systems among SME contractors in the Malaysian construction industry. The research objective is to analyze the traditional and e-tendering processes, identify challenges, and propose strategies for adoption. A mixed-methods approach was used, combining surveys with contractors in categories G3, G4, and G5, and interviews with industry experts. The research finds that while the e-tendering process shares similarities with traditional methods, its features and activities differ significantly. The main challenges identified include insufficient training and resistance to technological adaptation. To address these issues, the study suggests strategies such as offering training programs for employees and promoting digital knowledge to help SME contractors enhance their capabilities, improve tendering processes, and boost competitiveness.